Babel [videorecording (DVD)] - González Iñárritu, Alejandro; Pitt, Brad, 1963-; Blanchett, Cate, 1969-; García Bernal, Gael, 1978- (Paramount Home Entertainment, 2007)
A wealthy American is touring Morocco with his wife. The two become the focus of an international incident also involving a poor Moroccan farmer who is struggling to keep his two young sons in line and his family together. A San Diego nanny, with her employers absent, makes the disastrous decision to take her charges with her to a wedding in Mexico. A deaf-mute Japanese teen tries to deal with a relationship with her father and the world in general that has been upended by the death of her mother. It's about a gun. It's about communication - or the lack of it - both intercultural and intracultural. Raises issues like terrorism and immigration, and is as basic as husbands talking to their wives and parents understanding their children.